The Role of Complement C3 and C5a in Hyperinflammation, Cytokine Storm, and Immune Dysregulation during Severe COVID-19 Infection - Karim-ur-Rahman; Ali, Syed Shaukat; Murad, Shiza; Saba, Iram; Shireen, Farah; Rahman, Bushra; Lodhi, Muneeza; Khalid Farooqi, Muhammad Bilal Bin; Gamaryani, Asim (Indus Journal of Bioscience Research, 2025)
Severe COVID-19 is characterized by an excessive inflammatory response, often leading to acute respiratory distress syndrome (ARDS), multi-organ dysfunction, and high mortality. The complement system, particularly components C3 and C5a, has emerged as a critical driver of hyper inflammation and immune dysregulation in severe cases. This study aimed to investigate the roles of C3 and C5a in relation to disease severity, inflammatory markers, cytokine profiles, and clinical outcomes in hospitalized COVID-19 patients. A prospective observational study was conducted involving 150 participants: 60 with severe COVID-19, 60 with moderate disease, and 30 healthy controls. Plasma levels of C3 and C5a were measured using ELISA, while cytokines (IL-6, TNF-α, IL-1β, IFN-γ) were quantified via multiplex immunoassays. Additional clinical parameters, including CRP, ferritin, and hospital stay duration, and need for mechanical ventilation, were recorded. Correlation analyses were performed to explore associations between complement activity and disease outcomes. Both C3 and C5a levels were significantly elevated in severe COVID-19 patients compared to moderate cases and controls (p < 0.001). C5a showed strong positive correlations with IL-6 (r = 0.78) and hospital stay duration (r = 0.59). Patients with high C5a levels had longer hospitalizations and were more likely to require mechanical ventilation. Elevated complement levels also correlated with increased CRP, ferritin, and SOFA scores. Complement over activation, particularly C5a, is strongly associated with hyperinflammation, immune dysregulation, and poor outcomes in severe COVID-19. Targeting the complement cascade may offer a promising therapeutic strategy and aid in clinical risk stratification.